Is There a Potential Therapeutic Role for Caveolin-1 in Fibrosis? - Shihata, Waled A.; Putra, Mohammad R. A.; Chin-Dusting, Jaye P. F. (Frontiers in Pharmacology, 2017)
Fibrosis is a process of dysfunctional wound repair, described by a failure of tissue regeneration and excessive deposition of extracellular matrix, resulting in tissue scarring and subsequent organ deterioration. There are a broad range of stimuli that may trigger, and exacerbate the process of fibrosis, which can contribute to the growing rates of morbidity and mortality. Whilst the process of fibrosis is widely described and understood, there are no current standard treatments that can reduce or reverse the process effectively, likely due to the continuing knowledge gaps surrounding the cellular mechanisms involved. Several cellular targets have been implicated in the regulation of the fibrotic process including membrane domains, ion channels and more recently mechanosensors, specifically caveolae, particularly since these latter contain various signaling components, such as members of the TGFβ and MAPK/ERK signaling pathways, all of which are key players in the process of fibrosis. This review explores the anti-fibrotic influences of the caveola, and in particular the key underpinning protein, caveolin-1, and its potential as a novel therapeutic target.